2019
DOI: 10.1007/s42452-019-1191-z
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of end milling on Al–SiC-fly ash metal matrix composite using Topsis and fuzzy logic

Abstract: Metal matrix composites are extensively used in aerospace, automobile and other engineering applications as an alternative to a wide range of elements. High strength-weight ratio, durability and high corrosion resistance are benefits of metal matrix composites. The study that exhibits adopts optimal cutting parameters (speed, feed and depth of cut). The initial study is to explore end milling process of alumina (AA6082 with SiC 3% and fly ash 2%) molted metal matrix composite. The technique for order preferenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Apart from the implementation of parametric optimization of machining parameters during metal cutting, fuzzy TOPSIS was effective in various areas such as multi-response optimization of blended polymer composites (Şimşek and Uygunoğlu, 2016), optimization of drilling parameters for Al2O3 particles and sisal fiber-reinforced epoxy composites (Kamaraj et al ., 2018), optimization of the input parameters such as pulse on time, duty cycle, discharge current, etc. in the electron discharge machining process (Roy and Dutta, 2019) and optimization of the machining parameters of metal matrix composites (Al–SiC-fly ash) (Tamiloli et al ., 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Apart from the implementation of parametric optimization of machining parameters during metal cutting, fuzzy TOPSIS was effective in various areas such as multi-response optimization of blended polymer composites (Şimşek and Uygunoğlu, 2016), optimization of drilling parameters for Al2O3 particles and sisal fiber-reinforced epoxy composites (Kamaraj et al ., 2018), optimization of the input parameters such as pulse on time, duty cycle, discharge current, etc. in the electron discharge machining process (Roy and Dutta, 2019) and optimization of the machining parameters of metal matrix composites (Al–SiC-fly ash) (Tamiloli et al ., 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the cutting tool length to diameter is large and complex curved surface parts processing, the conventional method of milling cutter are prone to deformation, able to withstand the radial cutting force is small, in order to avoid the flutter, affect the machining accuracy and other negative effect to adopt conservative cutting parameters, such as reducing cutting speed, cutting depth and cutting width, this limits the processing efficiency. In the process of interpolation and milling, the tool is fed along the spindle direction, and the rigidity of the cutting system is large, which can better avoid chatter, make the machining quality of parts more stable, and improve the cutting parameters appropriately to improve the material removal rate [14][15].…”
Section: Interpolation and Milling Machining Mode And Modelingmentioning
confidence: 99%
“…Sidhu and Yazdani [11] employed desirability function and lexicographic goal programming to identify the optimal machining condition for having minimum residual stress, tool wear rate (TWR) and maximum material removal rate (MMR) during electrical discharge machining (EDM) of SiC/A359 MMC. Tamiloli et al [12] integrated fuzzy logic with technique for order of preference by similarity to ideal solution (TOPSIS) for optimization of the end milling parameters while machining Al-SiC-fly ash MMC. It was observed that feed rate, speed and depth of cut would significantly affect surface roughness and cutting force during the machining operation.…”
Section: Introductionmentioning
confidence: 99%